Advances in harmonic analysis and partial differential equations : AMS special session on Harmonic Analysis and Partial Differential Equations, April 21-22, 2018, Northeastern University, Boston, MA - Danielli, Donatella, 1966-; Mitrea, Irina (Contemporary mathematics (American Mathematical Society) ;, 2020)
"The back-up contains a draft title page, copyright page, toc, and preface"--